Magnesium depletion score and gout: insights from NHANES data - Cao, Xu; Feng, Haixia; Wang, Huijie (Frontiers in Nutrition, 2024)
Objectives: Gout is associated with hyperuricemia, and serum magnesium levels are negatively correlated with uric acid levels. Magnesium intake is also associated with a reduced risk of hyperuricemia. However, the relationship between the magnesium depletion score (MDS), which represents the systemic magnesium status, and gout is unclear. This study was conducted to investigate the association between MDS and gout as well as explore the impact of dietary magnesium intake on this relationship.We analyzed 18,039 adults with gout data who participated in the National Health and Nutrition Examination Survey between 2007 and 2016. Magnesium deficiency status was assessed using the MDS, a comprehensive scoring tool. Considering the possible effects of dietary magnesium intake, weighted multivariable logistic regression and subgroup analyses were used to assess the correlation between MDS and gout.The overall prevalence of gout among adults in the United States between 2007 and 2016 was 4.7%. After adjusting for confounders, MDS and gout risk showed a significant positive correlation. Individuals with an MDS of 2 and ≥3 had higher odds of gout than those with an MDS of 0 (MDS = 2, odds ratio: 1.86 [1.18-2.93], P = 0.008; MDS = 3, odds ratio: 2.17 [1.37-3.43], P = 0.001; P for trend <0.001). Dietary magnesium intake did not moderate the correlation between MDS and gout risk.A positive correlation exists between magnesium deficiency, as quantified using the MDS, and gout risk among adults in the US. Additionally, dietary magnesium intake did not alter this association.